Kurtosis and Skewness at Instructional Leadership Relationships Organizational Culture Organizational Commitment to Teacher Performance in the Junior High School - Amri, Ulil; ., Nellitawati; ., Syahril; Rusdinal,; Gistituati, Nurhizrah; Marsyidin, Sufyarma (Journal of Ecohumanism, 2024)
This research shows that the kurtosis and skewness values derived from the analysis of instructional leadership, organizational culture, and organizational commitment instruments related to teacher performance are normally distributed. The study employed a descriptive quantitative method, involving a sample of 357 teachers determined using Slovin's formula with a stratified random sampling technique. Data collection was conducted through questionnaires and analyzed using descriptive statistical analysis. The prerequisite tests for analysis included kurtosis and skewness values. The data analysis was carried out using SMART PLS 4 software. The results indicated that the kurtosis values demonstrated normal distribution, even though the skewness values were negative. The kurtosis values were considered normally distributed as they exceeded 3, while the negative skewness values indicated a tendency to not fully meet the normality assumption for the population and sample under specific conditions.